Angels & angelology in the Middle Ages - Keck, David, 1965- (OUP E-Books., 1998)
Angels have made a remarkable comeback in the popular imagination; their real heyday, however, was the Middle Ages. This text offers a study of angels and angelology in the Middle Ages, seeking to discover how and why angels became so important in medieval society.